Aplicabilidade da prisão preventiva de ofício na Lei Maria da Penha – Lei nº11340/06 - Barbosa, Vágner Pereira (2024)
This work proposes to examine the consequences of the changes promoted by the Anti-Crime Package in relation to the Maria da Penha Law and the autonomy of the individuals involved, through the method of bibliographic procedure and hermeneutic approach method. Law No. 13,964/2019 implemented changes to the national legal system that negatively affected the autonomy and protection system for women, established by Law No. 11,340/2006. The new distribution of responsibilities among judges in criminal proceedings, specifically the figure of the guarantee judge, could be harmful for women victims of violence, unless the guarantee judge also has specialization in the area. Preventive detention, provided for in article 20 of Law 11,340/2006, was not implicitly annulled and must be adjusted to article 311 of the Code of Criminal Procedure, allowing the judge to order preventive detention on his own initiative at any stage of the criminal process.